Color and Aroma Sensory Tests on the Hedonic Method of Rosella (Hibiscus Sabdaiiffa L.) Essential Oil - Nunuk Helilusiatiningsih; Titik Irawati; Muhamad Alwi Shahara (PT FORMOSA CENDEKIA GLOBAL, 2023)
The rosella plant functions as a remedy for hypertension, diabetes and diuretics. The aim of this study was to test the hedonic color and aroma of rosella essential oil. Research method: hedonic test. The results: Flower Petals (%) ( really like 60, like 40 , Aroma (%) : really like 55, like 45. Roselle Leaf Oil (%) : really like 25, like 75, Aroma (%) : really like 30, likes 70, ; Rosella seeds: color (%) : really likes 15, likes 85, aroma (%) : really likes 15, likes 85, ; Roselle stems : color (%) : really likes 30, likes 70, aroma (% ) really liked 15, liked 85, ; Rosella root: Color (%) really liked 25, liked 75, Aroma (%) : really liked 15, liked 85, So rosella flower petals were the best.